Prevalence of Entamoeba Histolytica infection in patients with colitis (Ulcerative and Infective) - Farhan Al-Rwi, Luay I.; Hassan Alakori, Maher M.; Abdulghafour, Kifah H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Ulcerative colitis (UC) is a chronic inflammatory disorder of the colon that often extends to involve the remainder of the large intestine in a continuous manner. Intestinal amoebiasis can present as a chronic, dysenteric syndrome of diarrhea, weight loss, and abdominal pain that can last for years and mimic ulcerative colitis.Objective: Studying the prevalence of E..histolytica by using serological method ELISA for their detection, Investigate the possible role of E.histolytica as a cause of blood, diarrhea in non-ulcerative colitis group &Comparison between serological detection of E.histolytica and stool examination.Patients and Methods: Retrospective and prospective study was conducted on 48 patients (18 males, 30 females); 30 patients were diagnosed as ulcerative colitis and 18 as non ulcerative colitis patients by endoscopy, histopathology, radiology and laboratory examinations at Gastroenterology and Hepatology Teaching Hospital through the period between January 2008 and June 2008. From all patients and control, a detailed medical history was taken; routine examination and relevant investigations were done. Blood and fresh stool specimens were collected from all patients and control. General stool examination and ELISA tests for IgG anti E.histolytica antibodies were assessed. Results: Histological typing of ulcerative colitis grouped into chronic ulcerative colitis 42 cases(86.67%) and active on chronic ulcerative colitis 6 cases (13.33%). By general stool examination, E.histolytica was positive in (70%) of ulcerative colitis (53.33% cyst and 16.67% trophozoit) and results of ELISA test for IgG anti E.histolytica antibodies was significant compared with control group (P < 0.05). General stool examination and IgG anti- E histolytica antibodies has been found that 75.8% of patients have positive IgG and cyst stage, and 77.8% were have positive IgG and trophozoit stage , while 24.2% of negative GSE results were also negative for IgG anti-E.histolytica antibodies, and the association was significantcompared with control group (P < 0.05).Conclusion: E.histolytica IgG Abs were significantly higher in ulcerative colitis compared to non ulcerative colitis group .Close association between E.histolytica and ulcerative colitis also there is a high incidence of E.histolytica among group of non ulcerative colitis patients. Sensitivity of detection of E.histolytica by ELISA and GSE is rather equal.